Ahya Coco: Terminal year end report - Dee, Yanna Kacey P. (Animo Repository, 2022)
Ahya Coco Organic Food Manufacturing Corp., or better known as Ahya Coco, is a coconut food and beverage manufacturing and exporting company from Davao City, which is known as the coconut capital of the Philippines. The company was first conceptualized in the year 2008 by one of the board of directors of the LKT group of companies, Ahya Coco’s parent company, wherein the inspiration came during their industry scanning as they decide on what new venture they should pursue. After much thought, the company decided that it was a good idea to establish a coconut business in Davao City named Ahya Coco, a business name combining the two words ahya and coco where the word ahya, a chinese word meaning older brother in english, signifies LKT’s founder’s eldest son as Ahya Coco’s founder, and the word coco which symbolizes their coconut business. In 2016, Ahya Coco opened their business and catered to the international markets of countries such as the USA, China, and Japan. Today, Ahya Coco has been operating for five years in the industry, however, their financial growth has been weak and quite stagnant in comparison to other coconut companies from the Philippines. The current pandemic situation did not help either as exportation restrictions and fees made it challenging for the company to adapt to the situation, making it impractical to continue relying on their exporting operations to produce financial security. The company also tried tapping the Davao markets by looking for groceries and supermarkets to keep the family business going, however, this only resulted in little improvement due to their lack of background and familiarity with the Philippine market which hindered them to plan out better strategies on their own. If this problem keeps going in the long run, Ahya Coco’s operations might lead to bankruptcy, making all their assets and hard work go to waste. However, after analyzing both the internal and external environment of Ahya Coco, it was determined that the company still has a potential to bounce back and achieve greater milestones in their existence. Through the internship, the group can help the family business grow by expanding their business in the local market and achieving brand awareness nationwide by introducing their products to retail stores and to the E-commerce industry in the Philippines. To be able to achieve this, different activities will be proposed to the company which includes forming and improving their marketing strategies and materials, developing a new product fit for the local market to further satisfy customers, setting up a new distribution channel for their business, assisting them in handling their employees, and organizing their finances, all of which are focused on gaining brand awareness in the Philippines and obtaining financial growth for the company during and after the group’s internship program in the business. With this, the family business growth plan prepared by the group will help Ahya Coco not just adapt and flourish in the local market, but to also remain relevant for generations to come.